FEATURES OF PSYCHOMOTOR DEVELOPMENT OF CHILDREN WITH SPEECH DEFECTS ALALIA - Z. G. Azhimova (European Journal of Humanities and Educational Advancements, 2024)
The cause of Alalia’s speech defect is damage to the spinal cord of the brain. With alalia, defects in the development of mental and motor skills may be observed, along with a lack of development of the speech language of children